Introduction - Lund, Jacob (The Nordic Journal of Aesthetics, 2017)
Welcome to the second issue of the re-designed Nordic Journal of Aesthetics. Although this issue is without an overall theme the five articles it comprises are more or less explicitly connected through their historically informed analyses and reflections on different dynamics of the relationship between aesthetics and politics that are currently in operation.